A Synopsis of Serum Biomarkers in Cutaneous Melanoma Patients - Pierre Vereecken; Frank Cornelis; Nicolas Van Baren; Valérie Vandersleyen; Jean-François Baurain (Hindawi Limited, 2012)
Many serum biomarkers have been evaluated in melanoma but their clinical significance remains a matter of debate. In this paper, a review of the serum biomarkers for melanoma will be detailed and will be discussed from the point of view of their practical usefulness. The expression of biomarkers can be detected intracellularly or on the cell membrane of melanoma cells or noncancer cells in association with the melanoma. Some of these molecules can then be released extracellularly and be found in body fluids such as the serum. Actually, with the emergence of new targeted therapies for cancer and the increasing range of therapeutic options, the challenge for the clinician is to assess the unique risk/response ratio and the prognosis for each patient. New serum biomarkers of melanoma progression and metastatic disease are still awaited in order to provide efficient rationale for followup and treatment choices. LDH as well as S100B levels have been correlated with poor prognosis in AJCC stage III/IV melanoma patients. However, the poor sensitivity and specificity of those markers and many other molecules are serious limitations for their routine use in both early (AJCC stage I and II) and advanced stages of melanoma (AJCC stage III and IV). Microarray technology and proteomic research will surely provide new candidates in the near future allowing more accurate definition of the individual prognosis and prediction of the therapeutic outcome and select patients for early adjuvant strategies.